Slovakia and its environmental transformation: measuring environmental attitudes using the new ecological paradigm - Marcineková, Lenka; Štěrbová, Martina; Výbošťok, Jozef; Hajdúchová, Iveta; Giertliová, Blanka; Šulek, Rastislav; Sarvašová, Zuzana; Šálka, Jaroslav (Frontiers in Psychology, 2024)
The New Ecological Paradigm (NEP) has been repeatedly used for the analysis of public environmental attitudes, as the public pays increased attention to the environmental issues, sustainability, or the climate crisis, and so on. Our paper deals with the use of the NEP to study and identify public environmental attitudes in the Slovak Republic. We discovered a deviation of our results from the NEP, as we identified altered environmental attitudes, which we find acceptable, as environmental attitudes are a delicate set of values encompassing different, yet interrelated facets. According to our results, we were able to classify our respondents into those with technocentric, ecocentric, and resiliocentric attitudes, while up to 70% of respondents hold the ecocentric attitude. The NEP has proven to be an important predictive tool in assessing public environmental attitudes to determine readiness for environmental transformation. However, we recommend using it with a combination of analysis of the impact of demographic factors analysis.